Factors associated with consistent condom use and STIs among foreign female entertainment workers: results from a cross-sectional survey in Singapore. (7th July 2016) - Lim, Raymond Boon Tar; Wong, Mee Lian; Cheung, Olive N Y; Tham, Dede Kam Tyng; Tai, Bee Choo; Chan, Roy
Abstract : Objectives: We assessed the prevalence of consistent condom use and laboratory-confirmed STIs among foreign female entertainment workers (FEWs) who engaged in paid or casual sex in Singapore and the factors associated with these characteristics. Methods: A cross-sectional survey, using time-location sampling, was conducted on 220 FEWs (115 Vietnamese and 105 Thai) in 2015. For multivariable analysis, we used a mixed-effects Poisson regression model with backward stepwise approach to account for clustering by venue and to obtain the adjusted prevalence ratios (aPRs) of factors associated with consistent condom use and STI positivity, respectively. Results: Consistent condom use with paid or casual partners in the past month was 39.6% and 36.2% for vaginal and oral sex, respectively. The prevalence of STI (cervical chlamydia, cervical gonorrhoea or pharyngeal gonorrhoea) positivity was 13.6%. In multivariable analysis, consistent condom use for both vaginal and oral sex increased with high self-perceived risk of getting STI/HIV (vaginal: aPR 2.09; 95% CI 1.26 to 3.46; oral: aPR 2.41; 95% CI 1.23 to 4.69) and condom negotiation (vaginal: aPR 3.74; 95% CI 2.07 to 6.75; oral: aPR 2.81; 95% CI 1.51 to 5.26). STI positivity decreased with consistent condom use for vaginal sex (aPR 0.22; 95% CI 0.07 to 0.75) and increased with number of sexual partners (aPR 1.43; 95% CI 1.07 to 1.92). Conclusion: In addition to advocating for policy decisions to provide a safer work environment, behavioural interventions on condom negotiation skills and condom use and biomedical interventions on STI/HIV testing and treatment interventions are needed among the FEWs in Singapore. Trial registration number: NCT02780986; pre-results.